2011
DOI: 10.1063/1.3607603
|View full text |Cite
|
Sign up to set email alerts
|

Particle-based multiscale coarse graining with density-dependent potentials: Application to molecular crystals (hexahydro-1,3,5-trinitro-s-triazine)

Abstract: We describe the development of isotropic particle-based coarse-grain models for crystalline hexahydro-1,3,5-trinitro-s-triazine (RDX). The coarse graining employs the recently proposed multiscale coarse-graining (MS-CG) method, which is a particle-based force-matching approach for deriving free-energy effective interaction potentials. Though one-site and four-site coarse-grain (CG) models were parameterized from atomistic simulations of non-ordered (molten and ambient temperature amorphous) systems, the focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 63 publications
5
48
0
Order By: Relevance
“…We are pursuing a bottoms-up method to develop these potentials (known as MS-CG), which effectively homogenizes atomistic information obtained from either QMD or classical MD into a particle based CG model. The details of this methodology and applications to nitromethane and RDX are detailed in recent publications [11,12]. In these, we have shown that CG MD results for structural, vibrational and elastic properties are in good agreement with atomistic simulation results for these systems, as well as agreement of shock properties, thus validating proper homogenization.…”
Section: Linking the Scalessupporting
confidence: 62%
“…We are pursuing a bottoms-up method to develop these potentials (known as MS-CG), which effectively homogenizes atomistic information obtained from either QMD or classical MD into a particle based CG model. The details of this methodology and applications to nitromethane and RDX are detailed in recent publications [11,12]. In these, we have shown that CG MD results for structural, vibrational and elastic properties are in good agreement with atomistic simulation results for these systems, as well as agreement of shock properties, thus validating proper homogenization.…”
Section: Linking the Scalessupporting
confidence: 62%
“…3 shows a superposition of the temperature profiles of shocked RDX at a single point in time for three simulations, as well as the corresponding snapshot of the molecular centers of mass positions from the atomistic simulation. These correspond to MD simulations using the atomistic model 7 , MD simulations using a CG model of RDX 13 , and DPD-E simulations using the same CG model of RDX. The positions of the shock fronts for the CG simulations are slightly behind that of the atomistic-MD simulations; note that the CG-MD simulation has a peak shock temperature that is 3,000 K higher than the atomistic-MD model (which melts the material).…”
Section: Cg Methods and Modelsmentioning
confidence: 99%
“…As a result, the exact values of temperatures may be affected. 23 Thus, the temperature values should not be taken literally, and rather represent a trend in a semi-quantitative way. A direct comparison of all-atom simulations with some of the CG-MD simulations will be done in the future.…”
Section: Columnar Nanocrystalline Petn: Other Loading Directions Amentioning
confidence: 99%
“…In this article, we report MD simulations of shock response of single crystal and nanocrystalline PETN using a CG model, which reduces computational cost while retaining reasonable accuracy, 20 necessary for simulations of large polycrystalline systems. Recently, Arman et al 51 applied a CG-MD shock simulations to polymers, and Izvekov et al 23 performed multiscale CG simulations on RDX. Our objective is to characterize in atomic detail the mechanical deformation at GBs and in grain interiors, and make connections to hotspot formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation